2008
DOI: 10.1002/col.20390
|View full text |Cite
|
Sign up to set email alerts
|

Color analysis of natural colorant‐dyed fabrics

Abstract: Colors from naturally dyed fabrics recently have attracted both consumers and manufacturers in fashion markets. Even though color attributes of the fabrics have been partially observed in some literature, a data base of colors for natural colorants in fabrics needs to be established and the colors to be characterized according to systematic color notations and tones in order to relate the traditional natural colors to contemporary color communication systems. Therefore, a study was performed to investigate col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
2
17
0
2
Order By: Relevance
“…As for most of specimens, values of L * indicating color lightness were relatively higher while those of C * meaning chroma referred to color saturation were lower. These are supported by some findings [7,8] that naturally dyed fabrics have seemed to be lighter and less strong in color.…”
Section: Experimental Preparation Of Specimenssupporting
confidence: 82%
See 2 more Smart Citations
“…As for most of specimens, values of L * indicating color lightness were relatively higher while those of C * meaning chroma referred to color saturation were lower. These are supported by some findings [7,8] that naturally dyed fabrics have seemed to be lighter and less strong in color.…”
Section: Experimental Preparation Of Specimenssupporting
confidence: 82%
“…In order to select specimens for yellowish and reddish color by natural dyeing, a total of 390 different 100 % silk fabrics (plain weave, 8.2 g/m 2 , 0.25 mm thickness) dyed with natural colorants reported in a previous study [8] were clustered by their CIELAB color values such as L * , a * , b * , C * , and h. Yellowish specimens were determined among the fabrics with Y or YR of Munsell's hue whereas reddish ones as those with R or RP. Four differently dyed fabrics for each hue group were finally chosen as specimens.…”
Section: Experimental Preparation Of Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural dyes are obtained from animals, insects, bacteria, fungi, minerals, and various parts of plants including roots, bark, leaves, flowers, and fruit (Haji 2012;Mongkholrattanasit et al 2013a). Natural dyes are known for their use in the coloration of food, cosmetics, leather, dye sensitizer, medicinal plants, and textile dyeing, and printing (Samanta and Agarwal 2009;Yi and Cho 2008). In the world today, the use of natural dyes for coloration has mainly been confined to artisan craftsmanship, small scale cottage level dyers, printers as well as to small scale exporters and producers, who deal with high-valued ecofriendly textile production and sales (Samanta and Agarwal 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Some studies have reported that colors obtained by natural dyeings are limited and the "intensity" of natural dyes is low. 8,9 The dominant hue family of natural-dyed material is yellowish followed by reddish and purple hues. Mordants and certain auxiliaries, such as metallic salts and chitosan, have been applied to natural-dyed material to improve the limitations in shade.…”
Section: Introductionmentioning
confidence: 99%